Corporate Social Responsibility – A Qualitative Study of Concept and Implementation Alignment in PT. XYZ - Margaret Diandra Sutanto (iBuss Management, 2013)
This study was accomplished in order to see if the CSR concept in PT. XYZ and how the management function as the indicator of the implementation shows alignment. Concepts of CSR were various that it leads to confusion. CSR in Indonesia is mandatory, but the law itself is not clear, therefore the companies were left to do CSR based on what they understood about CSR. Concept and implementation that is fully aligned is showing that the management of the company is capable of translating concept into implementation and capable of managing themselves as a business in order to sustain in business world. This is a qualitative research for the research was specific to phenomenon in PT. XYZ. This research is descriptive in nature for it is intended to observe the phenomenon in its natural setting. The data collection was conducted by semi-structured interview and moderate participatory observation. Analysis was based on the CSR Mapping of Garriga and Melé and CSR Typology of Kourula and Halme, which see CSR as the result of interaction of business and society.